Law Enforcement Against Policies Who Breached The Code Of Conduct - Alvi Syahri (Jurnal Daulat Hukum, 2020)
The purpose of this research to find out and analyze law enforcement against police officers who violate the code of ethics in carrying out their duties at Central Java Police, obstacles and solving obstacles. This study uses a sociological juridical approach with descriptive analysis research specifications. The data used are primary data and secondary data obtained through interviews and literature study. The data analysis method used is qualitative analysis. Furthermore, based on the research results it can be concluded: Law enforcement against police officers who violate the code of ethics in carrying out their duties at the Central Java Regional Police refers to Act No. 2 of 2002 concerning the Police, Government Regulation of the Republic of Indonesia Number 2 of 2003 concerning Disciplinary Regulations for Members of the National Police and Regulation of the Chief of Police No. Pol. 14 of 2011 concerning the Professional Code of Ethics for the State Police of the Republic of Indonesia. Several factors that hinder law enforcement against unscrupulous police officers who violate the code of ethics are divided into internal factors: Leaders who have not fully paid attention to the implementation of disciplinary law enforcement duties for Polri members, level of discipline, awareness and compliance of Polri members with binding disciplinary regulations and applies to him is still relatively low so that disciplinary violations keep happening, Polri's disciplinary law enforcement often appears to lack transparency. External factors: Lack of public awareness in conducting supervision and complaints when there are people who violate them.Keywords: Law Enforcement; Police Officers; Offenses; Code of Ethics.